Saturation Gain Characteristics of Quantum-Well Semiconductor Optical Amplifier - Al-mfrji, Alhuda A. (Nahrain University College of Engineering Journal, 2011)
Recently, there is an increasing interest onquantum well (QW) semiconductor optical amplifier in optical communications and optical signal processing applications. This paper addresses the dependence of saturation power on QW structure parameters. Expressions are given to assess this dependency and the resultsindicate that the saturation power is a decreasing function of number of wells, well thickness, and amplifier length and it is almost independent ofbarrier thickness.